The Effectiveness of Fluorescent Light Energy as Adjunct Therapy in Canine Deep Pyoderma: A Randomized Clinical Trial - Andrea Marchegiani; Alessandro Fruganti; Andrea Spaterna; Matteo Cerquetella; Adolfo M. Tambella; Susan Paterson (Veterinary Medicine International)
A single centre, single-blinded, prospective, randomized, controlled clinical study was conducted to evaluate the effectiveness of twice weekly fluorescent light energy therapy (Phovia™) as adjunct to systemic antibiotics in the management of deep pyoderma in dogs. Dogs with clinical lesions consistent with deep pyoderma, positive bacterial culture, and showing neutrophil engulfing bacteria at cytology were included in the study. Assessments were undertaken weekly for 8 weeks and every 2 weeks thereafter until 12 weeks after enrolment. At each visit, lesions were scored and cytology was conducted to determine a neutrophil engulfing bacteria score. All dogs (Groups A and B) were treated with systemic antibiotic twice daily, and Group B received additionally Phovia twice weekly. Median treatment duration was 11.7 weeks for Group A and 5.7 weeks for Group B. After 8 weeks of treatment, the percentage of dogs that achieved clinical resolution was 35.0% and 88.0% for Groups A and B, respectively. Lesion scores showed highly statistically significant difference in favour of Group B from week 3 to 8, and neutrophil engulfing bacteria scores showed statistical difference from week 2 onwards in favour of Group B. These results indicate that Phovia, when used as an adjunct to systemic antibiotics, can accelerate time to clinical resolution in cases of canine deep pyoderma.